2013
DOI: 10.1371/journal.pone.0063104
|View full text |Cite
|
Sign up to set email alerts
|

Complex Formation between NheB and NheC Is Necessary to Induce Cytotoxic Activity by the Three-Component Bacillus cereus Nhe Enterotoxin

Abstract: The nonhemolytic enterotoxin (Nhe) is known as a major pathogenicity factor for the diarrheal type of food poisoning caused by Bacillus cereus. The Nhe complex consists of NheA, NheB and NheC, all of them required to reach maximum cytotoxicity following a specific binding order on cell membranes. Here we show that complexes, formed between NheB and NheC under natural conditions before targeting the host cells, are essential for toxicity in Vero cells. To enable detection of NheC and its interaction with NheB, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 36 publications
2
51
0
2
Order By: Relevance
“…We are uncertain about the physiological consequences of this binding. A more recent study suggested that at higher concentrations, NheB attaches unspecifically to Vero cells, which may result in an inability to further form active complexes upon binding of NheC and NheA [23]. Our findings parallel these results.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We are uncertain about the physiological consequences of this binding. A more recent study suggested that at higher concentrations, NheB attaches unspecifically to Vero cells, which may result in an inability to further form active complexes upon binding of NheC and NheA [23]. Our findings parallel these results.…”
Section: Discussionsupporting
confidence: 91%
“…In a later study, however, the authors identified NheB binding using one assay but not another; additionally, NheC was described as a binding moiety [22]. Additionally, it was recently shown that in solution, NheB and NheC form complexes, and it was suggested that this complex, in addition to NheC alone, may bind to the cellular surface [23]. Thus, for both the Hbl and Nhe toxins, the binding order of toxin components and the mechanisms of pore formation are not clear.…”
Section: Introductionmentioning
confidence: 99%
“…The PEPperPRINT ® chip allows an assessment of binding to 849 possible overlapping 13 amino acid linear epitopes within the protein sequence of gp160 (Heilkenbrinker et al, 2013; Shukla et al, 2012). Based on averaged median foreground intensities, intensity maps were generated and antibody binding to the peptide map was highlighted by an intensity color code with red for high spot intensities (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The optimal ratio between the NheA, NheB, and NheC components appear to be about 10:10:1, respectively [87]. A ratio lower than 5:1 and higher than 50:1 between NheB and NheC strongly reduces cytotoxicity [70,86]. The complex formation between NheB and NheC is directly correlated with the relative concentrations.…”
Section: The Nonhemolytic Enterotoxin (Nhe)mentioning
confidence: 95%
“…Under natural conditions, NheB and NheC form a complex that seem to be necessary to induce cytotoxic activity, and to reach maximum cytotoxicity, the binding of the components follows a specific order on the cell membrane [70]. Due to the complex formation with NheB in solution, free NheC have never been detected in natural culture supernatants of B. cereus strains [66,70,81,87]. The optimal ratio between the NheA, NheB, and NheC components appear to be about 10:10:1, respectively [87].…”
Section: The Nonhemolytic Enterotoxin (Nhe)mentioning
confidence: 99%